2001
DOI: 10.1021/bi0102959
|View full text |Cite
|
Sign up to set email alerts
|

The srhSR Gene Pair from Staphylococcus aureus:  Genomic and Proteomic Approaches to the Identification and Characterization of Gene Function

Abstract: Systematic analysis of the entire two-component signal transduction system (TCSTS) gene complement of Staphylococcus aureus revealed the presence of a putative TCSTS (designated SrhSR) which shares considerable homology with the ResDE His-Asp phospho-relay pair of Bacillus subtilis. Disruption of the srhSR gene pair resulted in a dramatic reduction in growth of the srhSR mutant, when cultured under anaerobic conditions, and a 3-log attenuation in growth when analyzed in the murine pyelonephritis model. To furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 34 publications
5
104
0
1
Order By: Relevance
“…A fourth two-component system, SrrAB, recently identified by our group (18) and others (19), was found to inhibit RNAIII expression and may itself be repressed by agr. Mutants of srrAB are unable to grow normally under anaerobic conditions (18,19), and expression of srrAB was shown to regulate genes involved in energy metabolism (19).…”
Section: Figurementioning
confidence: 91%
See 1 more Smart Citation
“…A fourth two-component system, SrrAB, recently identified by our group (18) and others (19), was found to inhibit RNAIII expression and may itself be repressed by agr. Mutants of srrAB are unable to grow normally under anaerobic conditions (18,19), and expression of srrAB was shown to regulate genes involved in energy metabolism (19).…”
Section: Figurementioning
confidence: 91%
“…Mutants of srrAB are unable to grow normally under anaerobic conditions (18,19), and expression of srrAB was shown to regulate genes involved in energy metabolism (19). The signal for the system may be menaquinone, an intermediate in the oxidative respiratory pathway.…”
Section: Figurementioning
confidence: 99%
“…A study by Vetter and Schleivert demonstrated that the inactivation of BrrA dramatically reduced the synthesis of lethal factor, edema factor, and protective antigen; however, the group led by Perego failed to observe a decrease in protective antigen synthesis (229,232). In staphylococci, the ResDE homolog is known as the staphylococcal respiratory response (SrrAB, also known as SrhSR) (221,238).…”
Section: Srrabmentioning
confidence: 99%
“…In addition, SrrA binds to the promoter region of icaADBC and activates transcription under anaerobic conditions; thus, the inactivation of srrAB decreases PIA biosynthesis (226). Concomitant with a decrease in PIA biosynthesis, srrAB inactivation increases the expression of the TCA cycle enzymes aconitase, succinate dehydrogenase, and fumarase and NADH dehydrogenase (221). Our laboratory recently demonstrated that PIA is synthesized when TCA cycle activity is repressed (190,230); thus, the effect of srrAB on PIA biosynthesis is twofold, with the direct regulation of icaADBC transcription and indirect regulation via the repression of TCA cycle activity.…”
Section: Srrabmentioning
confidence: 99%
“…Although TRAP has its own promoter and termination site, the genes coding for two-component systems are usually located in the same operon. About 16 possible operons encoding two-component systems were identified in S. aureus (31,43,45), and many of these systems have not yet been fully characterized. It is possible that one of them might be involved in functional interactions with TRAP, using the latter as a putative phospho-relay.…”
Section: (Cat To Gct)mentioning
confidence: 99%